Agomelatine for the Treatment of Major Depressive Episodes in Schizophrenia-Spectrum Disorders: An Open-Prospective Proof-of-Concept Study. Issue 6 (December 2016) - Englisch, Susanne; Jung, Hanna Sophie; Lewien, Antje; Becker, Anna; Nowak, Ulrike; Braun, Hanna; Thiem, Jascha; Eisenacher, Sarah; Meyer-Lindenberg, Andreas; Zink, Mathias
Abstract : Background: Depressive episodes in schizophrenia constitute a major clinical problem, and treatment success is often limited by treatment-emergent side effects. Agomelatine, an agonist at melatonergic MT1 /MT2 receptors and 5-HT2C receptor antagonist, is a new antidepressant with a novel mode of action which constitutes a potential therapeutic option for depression in schizophrenia. Methods: Twenty-seven patients with lifetime diagnoses within the schizophrenia spectrum and comorbid depression were treated with agomelatine in addition to stable doses of antipsychotic agents. Severity of depression and other psychopathological domains (positive/negative symptoms, general psychopathology, psychosocial performance) was assessed regularly by means of standardized rating scales during a 6-week acute treatment phase as well as after a 6-week extension phase. Moreover, safety measures (electrocardiograms, laboratory counts, neurological and non-neurological side effects, sleep quality, sexual functioning) were monitored on a regular basis. Results: Depressive symptoms improved significantly during the 6-week acute treatment phase. In parallel, a significant improvement of negative symptoms, global psychopathology, and psychosocial performance was observed, whereas positive symptoms remained stable. Agomelatine was mostly well tolerated with predominantly mild and self-limiting side effects. However, pharmacokinetic interactions with antipsychotic agents were observed. Interestingly, the quality of sleep did not improve significantly, pointing toward mechanisms that do not depend on resynchronization of circadian rhythms. Conclusions: Agomelatine appears to be safe and efficacious in treating depressive symptoms in patients with schizophrenia. The risk of pharmacokinetic interactions with antipsychotic agents warrants the need of therapeutic drug monitoring, and regular recording of vital signs seems necessary. Further randomized trials will have to confirm these findings.